Exploring perceptions towards policy formulation in Indonesia waqf sector: an organizational legitimacy perspective - Listiana, Lisa; Syed Jaafar Alhabshi, Syed Musa; Osman@Hussin, Ahmad Zamri (2019)
The produced policies by waqf authority may apply to relevant stakeholders, such as registered waqf managers/institutions (muttawalis), waqf founders (waqifs), and waqf beneficiaries (mauquf alayhs). In consequence, those policies may directly or indirectly influence the waqf activity, waqf management, and waqf development in the country. Due to this implication, it is important to assess the policy and process of policy making by the waqf authority. Waqf authority need to acknowledge perceptions of their immediate stakeholders to evaluate their stance and to develop strategy in garnering organizational legitimacy. This study aims to explore perceptions of immediate stakeholders toward policy and policy formulation process in waqf sector. To this end, 3 Focus Group Discussions with 10 key informants from 4 different institutions in Indonesia are conducted. Collected data is analysed using thematic analysis. It is expected that current study can offer practical contribution by identifying main themes for evaluation for the waqf authority by accommodating views of practitioners in the field as their immediate stakeholders.